In vitro Antioxidant and Antimicrobial Pharmacological Investigations of Rhus coriaria L. (Sumac): A Review - SAKTHI PRIYADARSINI SETHURAMAN; GLENA ABDULLAH HAMAD; KAMARAJ RAJU (Iraqi Journal of Pharmaceutical Sciences, 2025)
Abstract